Answer:
[tex]f(x)=-21\sqrt{x+4}[/tex].
Step-by-step explanation:
We have been given a parent function [tex]f(x)=3\sqrt{x}[/tex]. We are asked to reflect our given function across the x-axis, vertically stretch by a factor of 7, shifted left 4.
We will perform the transformation in the given order.
First of all, we will reflect the function [tex]f(x)=3\sqrt{x}[/tex]. across x-axis.
We know that when a function g(x) is reflected x-axis it becomes [tex]-g(x)[/tex], so our function after reflection across x-axis would be [tex]f(x)=-3\sqrt{x}[/tex].
Now, we will vertically stretch the function.
We know that to stretch a function g(x) vertically, we need to multiply it by factor of stretch. So our function after vertical stretched by a factor of 7 would be [tex]f(x)=7(-3\sqrt{x})=-21\sqrt{x}[/tex].
To shift graph by 4 units to left, we will add 4 under square root function as:
[tex]f(x)=-21\sqrt{x+4}[/tex]
Therefore, our required function would be [tex]f(x)=-21\sqrt{x+4}[/tex].